2013
DOI: 10.4103/0970-9185.117053
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cervical spine movement during laryngoscopy with Macintosh and Truview laryngoscopes

Abstract: Background:Truview laryngoscope provides an indirect view of the glottis and will cause less cervical spine movement since a ventral lifting force will not be required to visualize the glottis compared to Macintosh laryngoscope.Materials and Methods:A randomized crossover study to assess the degree of movement of cervical spine during endotracheal intubation with Truview laryngoscope was conducted in 25 adult ASA-I patients. After a standard anesthetic technique laryngoscopy was performed twice in each patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…There was a significant difference between the two groups in the mean heart rate at minute 3 (p-value=0.03), the mean systolic/diastolic pressure at all minutes, and the mean SaO2 at minute 4 (p-value=0.003). In a study by Bhardwaj conducted in 2013 to evaluate cervical spine motion with a Macintosh laryngoscope and a Trueview laryngoscope, the authors found that the latter offered a better laryngoscopic view of the glottis and less cervical spine motion [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant difference between the two groups in the mean heart rate at minute 3 (p-value=0.03), the mean systolic/diastolic pressure at all minutes, and the mean SaO2 at minute 4 (p-value=0.003). In a study by Bhardwaj conducted in 2013 to evaluate cervical spine motion with a Macintosh laryngoscope and a Trueview laryngoscope, the authors found that the latter offered a better laryngoscopic view of the glottis and less cervical spine motion [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cervical spine movement during intubation is prevented by manual inline stabilization by an assistant throughout the procedure [44] . Use of McCoy laryngoscope, bougies and videolaryngoscope have been studied and found to have less cervical movement during intubation and should be preferred [30,[47][48][49] .…”
Section: Cervical Spine Injurymentioning
confidence: 99%
“…In addition, “in-line stabilization” worsens the laryngoscopic view which may, in turn, worsen the outcome in traumatic brain injury by delaying endotracheal intubation and causing hypoxia [ 15 , 16 ]. Using a video laryngoscope, instead of a conventional laryngoscope with a Macintosh blade, may be beneficial for intubating patients whose neck position needs to be in a neutral position and their cervical spine requires immobilization [ 17 19 ]. Neck movements during laryngoscopy using a conventional Macintosh laryngoscope has been compared to that using the GlideScope video laryngoscope [ 18 ] and the Truview PCD laryngoscope [ 19 ].…”
Section: Early Airway Maintenancementioning
confidence: 99%
“…Using a video laryngoscope, instead of a conventional laryngoscope with a Macintosh blade, may be beneficial for intubating patients whose neck position needs to be in a neutral position and their cervical spine requires immobilization [ 17 19 ]. Neck movements during laryngoscopy using a conventional Macintosh laryngoscope has been compared to that using the GlideScope video laryngoscope [ 18 ] and the Truview PCD laryngoscope [ 19 ]. The results of the two studies found that the number of neck movements is reduced when using the video laryngoscopes for endotracheal intubation.…”
Section: Early Airway Maintenancementioning
confidence: 99%